2009
DOI: 10.1007/s11738-009-0403-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of suadea salsa S-adenosylmethionine synthetase gene promotes salt tolerance in transgenic tobacco

Abstract: The suadea salsa full-length S-adenosylmethionine synthetase (SsSAMS2) was introduced into tobacco (Nicotiana tabacum L.) by Agrobacterium tumefaciensmediated transformation. The gene transformation and expression in tobacco were confirmed by PCR, RT-PCR and Northern blotting analysis. Several transgenic lines (ST lines) overexpressing SsSAMS2 gene under the control of cauliflower mosaic virus 35S promoter showed more seeds number and weight, and accumulated higher free total polyamines (PAs) than wild-type pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 42 publications
1
50
0
2
Order By: Relevance
“…Because SAM is an important factor in primary and secondary metabolism, various effects may be explained via plant transformation with a SAMS gene (Belny et al 1997). SAMS genes under the control of the CaMV 35S constitutive promoter were introduced in Arabidopsis thaliana (Peleman et al 1989a, b), Papaver somniferum (Belny et al 1997), and Nicotiana tabacum (Boerjan et al 1994;Belbahri et al 2000;Qi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because SAM is an important factor in primary and secondary metabolism, various effects may be explained via plant transformation with a SAMS gene (Belny et al 1997). SAMS genes under the control of the CaMV 35S constitutive promoter were introduced in Arabidopsis thaliana (Peleman et al 1989a, b), Papaver somniferum (Belny et al 1997), and Nicotiana tabacum (Boerjan et al 1994;Belbahri et al 2000;Qi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It had been verified that the overexpression of SAMS could effectively improve the stress tolerances, i.e. cold stress and salt stress of plant (Sodabeh et al, 2013, Qi et al, 2010. Based on the results aforementioned, another role of SAMS was to implicate in the tolerance to drought stress, and AM symbiosis of pigeon pea might up-regulated the expression of CcSAMS, which at least partially lead to the elevated tolerance to drought stress in this species.…”
Section: Figmentioning
confidence: 92%
“…1). Previous study has reported that two SAMS signature motifs, GAGDQGHMFGY and GGGAFSGKD, are conserved among many species (Hilti et al 2000;Qi et al. 2010).…”
Section: Amino Acid Sequence Analysis and Alignmentmentioning
confidence: 99%
“…Functional studies have shown the effects of SAMS on abiotic stress. For example, overexpression of SAMS in alfalfa and tobacco could improve their salinity tolerance (Qi et al 2010;Hua et al 2012). Low temperature conditions can induce the expression of SAMS in O. sativa, A. thaliana, and Zea mays (Cui et al 2005;Yang et al 2006;Uváčková et al 2012).…”
Section: Introductionmentioning
confidence: 99%